Microplastic Analysis in Digestive Tracts of Baronang and Goatfish in Kuta Lombok - Jasanti, Ninsanti Aura; Zulkifli, Lalu; Bahri, Syamsul; Karnan, Karnan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Microplastic pollution has become a significant environmental problem in marine ecosystems, particularly in coastal areas impacted by increased anthropogenic activity. The coastal waters of Kuta, Lombok, are potentially exposed to plastic waste from tourism and fisheries, which can degrade into microplastics and enter the marine food chain. This study aims to identify the types, abundance, and characteristics of microplastics in the digestive tracts of rabbitfish (Siganus canaliculatus) and goatfish (Parupeneus multifasciatus). The study used a modified NOAA method for 60 fish samples, including hydrogen peroxide (H₂O₂) digestion and NaCl density separation, followed by microscopic observation. The results showed that microplastics were present in both fish species, consisting of fiber and fragment types, with fibers being the dominant type. Microplastic abundance was relatively low, at 0.6 particles/individual in rabbitfish and 0.5 particles/individual in goatfish. The dominant colors observed were black, blue, and red. These findings indicate that microplastic contamination has occurred in the study area, albeit at a relatively low level. Therefore, better plastic waste management and increased public awareness are recommended to reduce further contamination in coastal ecosystems.